A test field for Gaia: radial velocity catalogue of stars in the south ecliptic pole - Frémat, Yves; Altmann, Martin (Arxiv, 2016)
Gaia is a space mission currently measuring the five astrometric parameters as well as spectrophotometry of at least 1 billion stars to G = 20.7 mag with unprecedented precision. The sixth parameter in phase space (radial velocity) is also measured thanks to medium-resolution spectroscopy being obtained for the 150 million brightest stars. During the commissioning phase, two fields, one around each ecliptic pole, have been repeatedly observed to assess and to improve the overall satellite performances as well as the associated reduction and analysis software. A ground-based photometric and spectroscopic survey was therefore initiated in 2007, and is still running in order to gather as much information as possible about the stars in these fields. This work is of particular interest to the validation of the Radial Velocity Spectrometer (RVS) outputs. The paper presents the radial velocity measurements performed for the Southern targets in the 12 - 17 R magnitude range on high- to mid-resolution spectra obtained with the GIRAFFE and UVES spectrographs.
Gesehen am 26.10.2017